The Influence of Menstrual Cycle Phases on Maximal Strength Performance in Healthy Female Adults: A Systematic Review with Meta-Analysis - Marc Niering; Nacera Wolf-Belala; Johanna Seifert; Ole Tovar; Jacqueline Coldewey; Jennifer Kuranda; Thomas Muehlbauer (MDPI AG, 2024)
Maximal strength is a significant factor in achieving peak performance and injury prevention in athletes. In individualization strategies for the efficient development of athletes, it is necessary to consider the respective components separately. The purpose of this study was to systematically examine the effects of the different cycle phases on isometric, isokinetic, and dynamic maximum strength. A systematic literature review was conducted; databases were searched from January 1960 to September 2023. The included studies focused on the expression of maximal strength in the earlier follicular phase as well as at least one comparative phase. Of the initial 707 articles identified, 22 met the selection criteria and were included. The studies considered a total of 433 subjects. Our results revealed medium effects (weighted mean standardized mean difference (SMD) = 0.60; seven studies) for isometric maximal strength in favor of the late follicular phase, small effects (weighted mean SMD = 0.39; five studies) for isokinetic maximal strength in favor of the ovulation phase, and small effects (weighted mean SMD = 0.14; three studies) for dynamic maximal strength in favor of the late follicular phase. The results indicate that the early follicular phase is unfavorable for all strength classes. Peak performance in isometric strength is seen in the late follicular phase, whereas isokinetic strength peaks during ovulation. Dynamic strength is optimal in the late follicular phase.